Tertiary nitrification of wastewater in trickling filters - Biddle, Jeremy R. (Cranfield University, 1994)
This study was designed to investigate, at laboratory and pilot scale, the effects of various loading and climatic factors on the nitrification perfon-nance of four media, and to undertake a comparative assessment of the media. The media used were blast furnace slag and three random plastic media: Flocor RS, Etapak 160 and a new medium, Etapak 210. Laboratory experiments using pure cultures of Nitrosomonas europaea have determined the effect on nitrification of temperature, pH and substrate, BOD and inhibitor concentrations. Optimal values have been resolved for the temperature and pH and half- saturation constants for the substrate and inhibition are calculated for pure culture conditions. The presence of glucose and glutamic acid has been shown to have a beneficial effect on nitrification, although this observation could not be adequately explained. Pilot scale research, conducted over a two year period, has provided an accurate representation of a nitrifying trickling filter by using effluent from Cranfield STW in filters exposed to the full climadc variation. Data obtained from these filters have indicated the superior performance of the blast furnace slag media due mostly to its ability to maintain a large active bacterial Population without excessive accumulation. Results have been used to support or challenge previous publications, and to generate a set of desion curves. Conclusions from this research have been used in the design of a full scale nitrifying trickling filter which has been constructed at Cranfield STW, early data from which are presented.